Congenital or infantile coxa vara - Motta, Heber; Schimchak, Mario (Cirugía del Uruguay, 1973)
There is an etyologic classification of infantile coxa vara which permits a relatively easy approach to the different manifestations of this syndrome. Present knowledge is as yet insufficient and it has not been established whether this disease is of congenital or acquired origin. A roentgenogram is conclusive in a diagnostics. The vertical cartilage is characteristic and it has both a diagnostic or a prognosis value. The radiographic aspect of the head and hip are normal in the first stages. In seroius cases sorne secondary disturbances of the hip may appear. The treatment must be made early. In severe cases valguisante osteotomy Scaglietti type is indicated; in mild cases, epiphyseodesis of the great.er trochanter as performed by Langenskii:ild.